Preclinical efficacy of sepantronium bromide (YM155) in multiple myeloma is conferred by down regulation of Mcl-1 - Wagner, Verena; Hose, Dirk; Seckinger, Anja; Weiz, Ludmila; Meißner, Tobias; Breitkreutz, Iris; Podar, Klaus; Ho, Anthony Dick; Goldschmidt, Hartmut; Krämer, Alwin; Raab, Marc-Steffen (OncoTarget, 2014)
https://doi.org/10.18632/oncotarget.2529 Verena Wagner, Dirk Hose, Anja Seckinger, Ludmila Weiz, Tobias Meißner, Thiery Rème, Iris Breitkreutz, Klaus Podar, Anthony D. Ho, Hartmut Goldschmidt, Alwin...